The influence of psychological empowerment on work engagement of civil servant employees in Padang city - Fhanesa Fatma Kharuniaesa; Suci Rahma Nio (Empathy : Jurnal Fakultas Psikologi, 2026)
Work engagement is a critical factor in enhancing employee performance, particularly in the public sector where service quality is a primary priority. However, maintaining high levels of work engagement remains a challenge, especially within bureaucratic organizational contexts. Drawing on the Job Demands–Resources (JD-R) Theory, psychological empowerment can be understood as a key personal resource that fosters employee motivation and engagement. This study aims to examine the effect of psychological empowerment on work engagement among public sector employees. A quantitative approach with a cross-sectional design was employed. Data were collected from 340 civil servants using purposive sampling techniques. Data analysis was conducted using simple linear regression. The results indicate that psychological empowerment significantly predicts work engagement (p < .001). The coefficient of determination (R² = .282) suggests that psychological empowerment accounts for 28.2% of the variance in work engagement. These findings highlight the important role of psychological empowerment as a personal resource in enhancing employee engagement, particularly within public sector organizations. Theoretically, this study contributes to the literature by providing empirical evidence from an emerging economy context and underscores the importance of strengthening psychological empowerment to foster higher levels of work engagement.